Pre-service EFL teachers’ perception on educational video production technology: A needs analysis - I'anatul Avifah; Muchamad Sholakhuddin Al Fajri (Institute of Advanced Engineering and Science, 2022)
This study conducted a needs analysis by investigating the perceptions of Indonesian pre-service English as a foreign language (EFL) teachers and in-service lecturers about instructional media development and the potential of educational video production for EFL teacher education. This research was conducted with a number of respondents from pre-service teachers who took instructional materials or media development course (IMALT/IMALD) and computer-assisted language learning (CALL) and lecturers including the program director of language education department in Indonesian universities. The results suggested that the design of the workshop should be devised as constructive learning with a focus on project-based learning to help teacher candidates develop their skills in employee value proposition (EVP). The workshop is also suggested to provide some examples of today’s educational video to bring into the discussion. In terms of the course design, the participants suggested some intended topics to learn, which are learning objectives and strategies, camera work, pedagogic approaches for video production, additional creative aids in video production and pre- and post-production phase of EVP.